Evaluasi Ketergunaan Aplikasi SIMPERTAN di Pustaka Bogor - Nurjannah Selly Kurnia; Nina Mayesti (Pustakaloka, 2019)
This research describes about the usability evaluation of SIMPERTAN application at PUSTAKA Bogor. SIMPERTAN is a web-based application that was developed by PUSTAKA to integrate the process of procurement, organize, service and circulation of library materials and became the union catalog for the PUSTAKA and the Library Institution in Balitbangtan scope. However, the usability of this application is still not optimal because Librarians at PUSTAKA still use other applications, such as WinISIS. Therefore, this study aims to evaluate how the usability of SIMPERTAN applications by librarians in PUSTAKA and the Library Institution in Balitbangtan scope under the guidance of LITERATURE in the Bogor region. This study uses quantitative approaches with quantitative descriptive methods. Data collection is done by survey method using a questionnaire. The results showed that the usability of SIMPERTAN application was in the high category. But there were a number of obstacles from the technical, system and librarian aspects, thus making SIMPERTAN usability less optimal.